Decreased Infectivity of a Neutralization-Resistant Equine Infectious Anemia Virus Variant Can Be Overcome by Efficient Cell-to-Cell Spread - Wu, Wuwei (American Society for Microbiology, 2011)
Two variants of equine infectious anemia virus (EIAV) that differed in sensitivity to broadly neutralizing antibody were tested in direct competition assays. No differences were observed in the growth curves and relative fitness scores of EIAVs of principal neutralizing domain variants of groups 1 (EIAV(PND-1)) and 5 (EIAV(PND-5)), respectively; however, the neutralization-resistant EIAV(PND-5) variant was less infectious in single-round replication assays. Infectious center assays indicated similar rates of cell-to-cell spread, which was approximately 1,000-fold more efficient than cell-free infectivity. These data indicate that efficient cell-to-cell spread can overcome the decreased infectivity that may accompany immune escape and should be considered in studies assessing the relative levels of fitness among lentivirus variants, including HIV-1.